Grammar and Corpora 2007 : selected contributions from the conference Grammar and Corpora, Sept. 25-27, 2007, Liblice = Gramatika a korpus 2007 : sborník příspěvků ze stejnojmenné konference, 25.-27.9.2007, Liblice - Štícha, František; Fried, Mirjam (Academia, 2008)
Sažetci na engleskom jeziku